2019
DOI: 10.1111/jcmm.14150
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin‐3 acts on the endothelial‐mesenchymal transition of heterotopic ossification in rats

Abstract: Despite the fact that extensive studies have focused on heterotopic ossification (HO), its molecular mechanism remains unclear. The endothelial‐mesenchymal transition (EndMT), which may be partially modulated by neuroendocrine cytokines is thought to play a major role in HO. Neurotrophin‐3 (NT‐3), which has neuroendocrine characteristics is believed to promote skeletal remodeling. Herein, we suggest that that NT‐3 may promote HO formation through regulation of EndMT. Here, we used an in vivo model of HO and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…EndoMT has been previously proposed to contribute to early phases of HO (51, 54, 59) and inhibition of EndoMT could rescue HO in vivo and in vitro (59). It has been suggested that the “transition” to a mesenchymal state in EndoMT and in Epithelial to mesenchymal transition (EMT), could indeed favor the acquisition of “stem-like” properties.…”
Section: Discussionmentioning
confidence: 99%
“…EndoMT has been previously proposed to contribute to early phases of HO (51, 54, 59) and inhibition of EndoMT could rescue HO in vivo and in vitro (59). It has been suggested that the “transition” to a mesenchymal state in EndoMT and in Epithelial to mesenchymal transition (EMT), could indeed favor the acquisition of “stem-like” properties.…”
Section: Discussionmentioning
confidence: 99%
“…NT-3 has been shown to promote osteogenesis by increasing BMP2-mediated Smad activation in BMSCs, while it inhibits collagen II expression and suppress chondrogenesis (132). However, NT-3 accelerates chondrogenesis of mesenchymal stem-like cells acquired from the endothelial progenitor cells underwent endothelial-mesenchymal transition, which serves an important role during heterotopic ossification (135). Similar to BDNF, NT-3 also promotes VEGF secretion of BMSCs and endothelial cells, partially through the PI3K/Akt signaling pathway; the enhanced vascularization effect accelerates diabetic wound healing and promotes bony repair at the injured growth plate (132,136).…”
Section: Schwann Cells and Neurotrophic Factors In Bone Metabolismmentioning
confidence: 99%
“…Previous studies have reported that tendon-derived stem cells (TDSCs) ( Jiang et al, 2017 ), hematopoietic stem cells and myofibroblasts are considered candidates for potential osteogenic cell types ( Zhang et al, 2016 ). In a recent study, vascular endothelial cells that undergo the endothelial-mesenchymal transition (EndMT) process were found to play a role in HO formation in injured Achilles tendons in rats ( Zhang et al, 2019 ). EndMT begins when endothelial cells delaminate from the organized cell layer and invade the underlying tissue, causing the loss of endothelial-specific markers, including vascular endothelial cadherin (VE-cadherin), cluster of differentiation 31 (CD31), tyrosine kinase with immunoglobulin-like and EGF-like 1 (Tie-1), and the gain of mesenchymal-specific markers, such as vimentin, neural cadherin (N-cadherin) and fibroblast-specific protein 1 (FSP-1).…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have suggested that under pathological conditions, vascular endothelial cells that undergo EndMT are able to acquire the differentiation potential of mesenchymal stem-like cells, and these endothelial-derived MSC-like cells contribute to HO formation by differentiating into chondrocytes and osteoblasts ( Medici et al, 2010 ; Medici and Olsen, 2012 ; Zhang et al, 2016 ). Recently, in a rat model of Achilles tendon injury, we observed the conversion of vascular endothelial cells into MSC-like cells through BMP-4- or TGF-β2-induced EndMT ( Zhang et al, 2019 ). Furthermore, these newly formed cells represented the dedifferentiation of endothelial cells into a stem cell phenotype, and cells of this phenotype can subsequently redifferentiate into osteoblasts and chondrocytes and contribute to HO formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation